Two‐Year Neurodevelopment and Growth Outcomes for Preterm Neonates Who Received Low‐Dose Intravenous Soybean Oil. Issue 2 (19th December 2017) - Ong, Margaret L.; Purdy, Isabell B.; Levit, Orly L.; Robinson, Daniel T.; Grogan, Tristan; Flores, Martiniano; Calkins, Kara L.
Abstract: Background : In some studies, the dose of intravenous soybean oil (SO) has been associated with a decreased incidence of intestinal failure–associated liver disease. The effect of lipid sparing on neurodevelopment (ND) and growth remains unknown. This study investigated the impact of SO dose on ND and growth over the first 2 years of age in preterm neonates. Materials and Methods : This is a single‐site prospective follow‐up study. Neonates with a gestational age ≤29 weeks were randomized to low‐dose (LOW) or standard‐dose (CON) SO. Bayley Scales of Infant Development III and anthropometric measurements were collected at approximately 6, 12, and 24 months corrected gestational age. Results : Subjects were premature, with a mean (±SD) gestational age of 28 ± 1 and 27 ± 1 weeks ( P = .3) for LOW and CON, respectively. Thirty subjects completed follow‐up (LOW = 15, CON = 15). There were no differences for ND and growth outcomes when LOW was compared with CON, with the exception of a higher 12‐month follow‐up cognitive scaled score in the LOW group ( P = .02). Conclusion : A reduced SO dose did not adversely affect ND or growth in this cohort of preterm neonates. However, larger studies are needed to determine the long‐term safety of SO dose reduction before this strategy can be adopted.